Breath-taking jobs: a case–control study of respiratory work disability by occupation in Norway. Issue 9 (30th June 2016) - Fell, AKM; Abrahamsen, R; Henneberger, PK; Svendsen, MV; Andersson, E; Torén, K; Kongerud, J
Abstract : Background: The current knowledge on respiratory work disability is based on studies that used crude categories of exposure. This may lead to a loss of power, and does not provide sufficient information to allow targeted workplace interventions and follow-up of patients with respiratory symptoms. Objectives: The aim of this study was to identify occupations and specific exposures associated with respiratory work disability. Methods: In 2013, a self-administered questionnaire was mailed to a random sample of the general population, aged 16–50, in Telemark County, Norway. We defined respiratory work disability as a positive response to the survey question: 'Have you ever had to change or leave your job because it affected your breathing?' Occupational exposures were assessed using an asthma-specific job-exposure matrix, and comparison of risks was made for cases and a median of 50 controls per case. Results: 247 workers had changed their work because of respiratory symptoms, accounting for 1.7% of the respondents ever employed. The 'breath-taking jobs' were cooks/chefs: adjusted OR 3.6 (95% CI 1.6 to 8.0); welders: 5.2 (2.0 to 14); gardeners: 4.5 (1.3 to 15); sheet metal workers: 5.4 (2.0 to 14); cleaners: 5.0 (2.2 to 11); hairdressers: 6.4 (2.5 to 17); and agricultural labourers: 7.4 (2.5 to 22). Job changes were also associated with a variety of occupational exposures, with some differences between men and women. Conclusions: Self-report and job-exposure matrix data showed similar findings. For the occupations and exposures associated with job change, preventive measures should be implemented.